Práxis pedagógica sócio-histórica: uma análise da atividade docente - Couto, Ligia Paula (2007)
This research focuses on the relationship between theory and pedagogical practice, more specifically the so called Socio-Historical Psychology. Such study aims at bridging the gap between socio-historical theory, based on Vygotsky s works, and Education, field of studies and practices, to verify how a college professor reflects upon this theory to analyze her own practice. To achieve this goal, a research methodology capable of yielding critical reflection was necessary. So, the collaborative inquiry methodology developed by Maria Cecília Camargo de Magalhães at LAEL PUC/SP and the autoconfrontation method elaborated by Yves Clot from CNAM in Paris contributed a great deal to the methodological organization. The researcher and the professor - subject of this research - chose a suitable course among those being taught by her. After that, three classes were video recorded; three episodes were selected out of these classes, all of them pointing to fundamental aspects of the sociohistorical theory. After transcribing these episodes and elaborating questions for an interview, the professor watched the videos, answering a set of previously elaborated questions after each episode. This interview with the teacher was also filmed and it was the material used in the analysis. The analysis showed that socio-historical principles have room in universities and that both collaborative inquiry and autoconfrontation method allow professors to reflect critically upon their pedagogical activity, collaborating to the building of praxis